High-performance polypropylene fiber anti-crack concrete and preparation method thereof
By introducing amino groups into polypropylene fibers and using nano-silica composites, the problems of uneven dispersion and insufficient bonding force are solved, and the crack resistance and durability of concrete are significantly improved.
Patent Information
- Application Number
- CN202411979379.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional concrete is prone to cracks under the action of external forces, and polypropylene fibers are unevenly dispersed and insufficient adhesion in concrete, resulting in poor crack resistance and strengthening effect.
Modified polypropylene fiber and nano-silica complex are used as anti-cracking agents, and amino groups are introduced into the polypropylene fibers through atomic transfer radical polymerization to enhance the hydrophilicity and surface energy of the fibers, and the fibers are evenly dispersed by dry stirring to form a three-dimensional chaotic distribution structure.
It significantly improves the crack resistance and durability of concrete, enhances the bonding force between the fiber and the concrete matrix, and improves the dispersion and density of fibers in concrete.
Smart Images

Figure BDA0005221171930000051 
Figure BDA0005221171930000071 
Figure BDA0005221171930000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building materials, and more specifically, to a high-performance polypropylene fiber crack-resistant concrete and a preparation method thereof. Background Art
[0002] As the most commonly used building material, concrete's crack resistance is of great significance to the safety and durability of the structure. However, traditional concrete materials are prone to cracks when subjected to external forces, which seriously affects the service life of the structure. At present, adding fiber materials to improve the crack resistance of concrete has become an effective method.
[0003] As a new type of fiber material, polypropylene fiber has the advantages of corrosion resistance, acid and alkali resistance, heat resistance and sunlight resistance. It can effectively improve the crack resistance and durability of concrete and is widely used in the preparation of fiber concrete.
[0004] With regard to the above-mentioned related technologies, the inventors found that although polypropylene fibers can improve the durability of concrete, in actual use, the fibers are often unevenly dispersed or difficult to disperse, resulting in insufficient bonding between the fibers and the concrete matrix. In certain specific circumstances, such as long-term water immersion or the effects of external factors such as carbonization, the bonding between the fibers and the cement matrix will also decrease, causing the concrete to crack easily and the anti-cracking reinforcement effect to be poor, which seriously affects the durability of the concrete. Summary of the invention
[0005] In order to improve the bonding force between polypropylene fibers and concrete matrix and enhance the crack resistance and durability of concrete, the present application provides a high-performance polypropylene fiber crack-resistant concrete and a preparation method thereof.
[0006] In the first aspect, the present application provides a high-performance polypropylene fiber anti-cracking concrete, which adopts the following technical scheme: a high-performance polypropylene fiber anti-cracking concrete, in which the raw materials include 200-300 parts of cement, 600-700 parts of aggregate, 120-180 parts of mineral doping materials, 5-7 parts of water reducer, 6-10 parts of expansion agent, 11-16 parts of anti-cracking agent and 86-172 parts of water in parts by weight; the anti-cracking agent is modified polypropylene fiber and nano-silicon dioxide in a mass ratio of (1.7-2.4):1.
[0007] By adopting the above technical solution, polypropylene fiber has excellent chemical corrosion resistance, weather resistance and high strength, and can form a three-dimensional random distribution in concrete. This distribution form enables the fiber to effectively withstand the internal stress caused by concrete shrinkage, temperature changes or external loads, thereby inhibiting the generation and development of micro cracks. It can also better absorb energy when concrete is subjected to external forces, reduce the generation and expansion of cracks, and effectively improve the crack resistance and durability of concrete.
[0008] Nano-silicon dioxide has a very high specific surface area and activity, and can react with calcium hydroxide in cement hydration products to generate calcium silicate gel. These gels fill the pores of cement paste, effectively improving the decrease in workability caused by the addition of modified polypropylene fibers, increasing the density of concrete, helping to reduce stress concentration and microcracks in concrete, and effectively improving the crack resistance and durability of concrete.
[0009] Optionally, the raw materials of the modified polypropylene fiber include 24-29 parts of polypropylene fiber, 16-21 parts of dimethylaminoethyl methacrylate, 0.08-0.14 parts of 2-bromopropionic acid and 0.15-0.25 parts of a catalyst in parts by weight; the catalyst is cuprous bromide and 2,2'-bipyridine in a mass ratio of 1:(1.4-1.8).
[0010] By adopting the above technical scheme, using dimethylaminoethyl methacrylate as a grafting monomer, 2-bromopropionic acid as an initiator, and a complex of cuprous bromide and 2,2'-bipyridine as a catalyst, the amino group is effectively promoted to be grafted and copolymerized on the surface of polypropylene fiber through atom transfer radical polymerization, thereby promoting the modification of polypropylene fiber.
[0011] The introduction of amino groups makes polypropylene fibers hydrophilic. During the concrete mixing process, the modified polypropylene fibers are easier to mix evenly with water, cement and other base materials, which effectively improves the dispersion of the fibers in the concrete matrix and avoids fiber agglomeration and sedimentation.
[0012] At the same time, the amino group can react with components such as cement hydration products to form chemical bonds or physical adsorption, significantly enhancing the bonding force between the modified polypropylene fiber and the concrete matrix.
[0013] In addition, the introduction of amino groups improves the polarity of polypropylene fibers, strengthens the cross-linking and interaction between the molecular chains of polypropylene fibers, and improves the thermal stability and fire resistance of polypropylene fibers. On the other hand, the amino groups combine with the polypropylene molecular chains through chemical reactions or physical mixing, reducing the number of combustible hydrocarbon segments in the fibers, which reduces the amount of heat and combustible gases released during combustion, thereby improving the fire resistance of polypropylene fibers.
[0014] Optionally, the method for preparing the modified polypropylene fiber comprises the following steps: S1: dispersing 2-bromopropionic acid in anhydrous pyridine to obtain a dispersion; S2: adding dimethylaminoethyl methacrylate and a catalyst to the dispersion, removing oxygen by nitrogen purging to form an activation solution; S3: adding polypropylene fiber to the activation solution, carrying out graft copolymerization reaction at 75-90° C. for 7-9 hours, and obtaining pretreated modified fiber after washing and vacuum drying; S4: Shearing the pretreated modified fibers to 3-5 mm to form short fibers; S5: Wrapping the short fibers around the surface of the pretreated modified fibers, and obtaining modified polypropylene fibers after curing. The mass ratio of the short fibers to the pretreated modified fibers is (3-5):1.
[0015] By adopting the above technical solution, the modified polypropylene fiber forms a structure in which short fibers wrap around long fibers, which increases the contact points between the fibers, thereby increasing the friction between the fibers, helping to improve the dispersion of the fibers in concrete, and providing more mechanical locking points for the combination between the modified polypropylene fiber and concrete, increasing the friction and physical bite between the fiber and the concrete matrix, thereby improving the bonding strength.
[0016] The long fibers are tightly wrapped and entangled by the short fibers as a skeleton. This structure can enhance the anchoring effect of modified polypropylene fibers in concrete. When the concrete is subjected to external forces, the long fibers and short fibers in the composite fiber structure can bear the load together, improving the crack resistance and durability of the concrete.
[0017] Optionally, the aggregate is basalt aggregate, including aggregate A and aggregate B in a mass ratio of (4-6):1; the aggregate A is 4.75-9.5 mm continuously graded crushed stone; the aggregate B is 9.5-13.2 mm continuously graded crushed stone.
[0018] By adopting the above technical solution and rationally matching basalt aggregates of different particle sizes, a multi-level skeleton structure is formed in the concrete, forming a more densely packed concrete structure. This helps to reduce the porosity inside the concrete, improve the density, enhance the durability of the concrete, and reduce stress concentration, so that the concrete can better maintain structural integrity and stability when subjected to external loads.
[0019] Optionally, the mineral doping material is selected from any one or more combinations of fly ash, silica fume, natural pozzolana and granulated blast furnace slag.
[0020] By adopting the above technical solution, fine particles of various mineral doping materials are evenly dispersed in the cement paste, becoming the core of a large number of hydrate precipitation. As the hydration age progresses, these fine particles and their hydration reaction products fill the pores of cement paste, improve the pore structure of concrete, make the internal structure of concrete more uniform and dense, and enhance the durability and crack resistance of concrete.
[0021] Optionally, the water reducer is a polycarboxylic acid high-efficiency water reducer.
[0022] By adopting the above technical solution, the use of polycarboxylic acid high-efficiency water reducing agent reduces the water-cement ratio of concrete, which helps to improve the fluidity and workability of concrete.
[0023] Optionally, the expansion agent is a UEA type expansion agent.
[0024] By adopting the above technical solution, the use of UEA type expansion agent compensates for the shrinkage of concrete, ensures that the concrete maintains volume stability during the hardening process, and improves the crack resistance of concrete.
[0025] In a second aspect, the present application provides a method for preparing high-performance polypropylene fiber crack-resistant concrete, using the following technical solution: A method for preparing high-performance polypropylene fiber crack-resistant concrete comprises the following steps: S1: Mix cement, aggregate, mineral doping material, modified polypropylene fiber and nano silicon dioxide, and stir evenly to form a premix; S2: Add water to the premix and stir to form an intermediate material; S3: Add water reducing agent and swelling agent to the intermediate material and continue stirring to obtain.
[0026] By adopting the above technical solution, the modified polypropylene fiber can be more easily evenly dispersed in a dry mixture of cement, aggregate, mineral doping material, etc. through a dry mixing method, thereby avoiding the problem of fiber agglomeration due to moisture in the wet mixing process.
[0027] When dry mixing concrete, modified polypropylene fibers form a three-dimensional random structure in the concrete, which can lock the moisture inside the dry mixture and enhance the bond strength of the concrete. This bond strength helps the fibers to better embed into the concrete matrix and form a tighter bond with the concrete matrix, significantly improving the concrete's crack resistance, wear resistance and durability.
[0028] Optionally, the modified polypropylene fiber is subjected to the following pretreatment before being mixed with other raw materials to form a premix: the modified polypropylene fiber is subjected to roller hot embossing treatment at 130-150° C. and 15-20 KPa to form a grid-like concave-convex texture on the surface of the modified polypropylene fiber.
[0029] By adopting the above technical solution, the surface of modified polypropylene fiber is printed by surface embossing technology, which can form a grid-like concave-convex texture on the surface of modified polypropylene fiber, effectively improving the surface roughness of the fiber. This significantly increases the contact area and mechanical interlocking force between the fiber and concrete, further improving the bonding force between the modified polypropylene fiber and the concrete matrix.
[0030] Optionally, the nano-silicon dioxide is subjected to the following pretreatment before being mixed with other raw materials to form a premix: the nano-silicon dioxide is dispersed in N,N-dimethylformamide, a halogenating agent and an alkali solution are added, the mixture is stirred for reaction for 20-24 hours, and the mixture is centrifuged, dried and ground to obtain the premix.
[0031] By adopting the above technical solution, halogen atoms have high electronegativity. Introducing halogen atoms on the surface of nano-silica can increase the surface activity of nano-silica, further improving the interaction between nano-silica and modified polypropylene fiber mixed with concrete matrix. Halogen groups can form chemical bonds with cement hydration products in concrete, such as halogens forming complexes with calcium ions, which can further enhance the chemical bonding between fiber and concrete.
[0032] In addition, halogen groups can promote the formation of a carbon layer under high temperature conditions. The carbon layer can protect the internal structure of the concrete, isolate the transfer of heat and oxygen, improve the fire resistance of the concrete, and make up for the defects of polypropylene fiber's poor fire resistance and flammability.
[0033] In summary, this application has the following beneficial effects: 1. The present application uses a composite of modified polypropylene fiber and nano-silicon dioxide as an anti-cracking agent. Amino groups are introduced into the polypropylene fiber through atom transfer radical polymerization to modify it, thereby enhancing the hydrophilicity of the polypropylene fiber, improving the surface energy of the polypropylene fiber, promoting the dispersion of the polypropylene fiber in the concrete and the bonding force between the polypropylene fiber and the concrete matrix, thereby improving the crack resistance and durability of the concrete.
[0034] 2. The present application introduces amino groups on the surface of polypropylene fibers and halogen groups on the surface of nano-silicon dioxide, which are helpful to compensate for the relatively low fire resistance and flammability of polypropylene fibers and improve the fire resistance of concrete.
[0035] 3. The method of the present application uses a dry mixing method to evenly disperse the modified polypropylene fibers in a dry mixture, thereby avoiding fiber agglomeration, and helping the modified polypropylene fibers to form a three-dimensional random structure in concrete after subsequent water addition, so that they are better embedded in the concrete matrix and improve the crack resistance and durability of the concrete. DETAILED DESCRIPTION
[0036] The present application is further described in detail below in combination with all preparation examples, embodiments and comparative examples.
[0037] raw material Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples in this application are all commercially available products, specifically: Cement is ordinary Portland cement, P42.5R; The aggregate is basalt aggregate, aggregate A is 4.75-9.5mm continuously graded crushed stone, and aggregate B is 9.5-13.2mm continuously graded crushed stone; Fly ash, which is Class II fly ash, has an average particle size of 20-25 μm; Silica fume, selected from Yiran, yr-1141; natural volcanic ash, selected from cisternite, 556; Granulated blast furnace slag, selected from Yaokai, KF-J7Y6, S95 grade ore powder; The water reducer is a polycarboxylic acid-based high-efficiency water reducer selected from Tuoda New Materials, TD-JSS; The expansion agent is a UEA type expansion agent selected from Tuoda, UEA555; Dimethylaminoethyl methacrylate, selected from Jieshikai Biotechnology, KA678406, with a purity of 98%; 2,2'-Bipyridine, selected from Shanghai Yuanye Biotechnology, S30285; N,N-dimethylformamide, selected from Jinan Hongteng Weiye New Materials, DMF05, with a purity of 99.9%; The halogenating agent is 2-bromoisobutyryl bromide, which is selected from Merrill Biotech, M10371.
[0038] Preparation example of modified polypropylene fiber Preparation Example 1 The modified polypropylene fiber, the raw materials and the amounts thereof are shown in Table 1, wherein the diameter of the polypropylene fiber is in the range of 0.02-0.05 mm, the length is in the range of 19-22 mm, and the catalyst is cuprous bromide and 2,2'-bipyridine in a mass ratio of 1:1.4.
[0039] Table 1 The method for preparing the modified polypropylene fiber comprises the following steps: S1: dispersing 2-bromopropionic acid in anhydrous pyridine to obtain a dispersion, wherein the mass ratio of 2-bromopropionic acid to anhydrous pyridine is 1:5; S2: adding dimethylaminoethyl methacrylate and a catalyst to the dispersion, removing oxygen by nitrogen purging to form an activation solution; S3: adding polypropylene fiber to the activation solution, carrying out graft copolymerization reaction at 80° C. for 8 h, and obtaining pretreated modified fiber after washing and vacuum drying; S4: Shearing the pretreated modified fibers to 3-5 mm to form short fibers; S5: Using the pretreated modified fiber as the main skeleton, the short fiber is wrapped and wound on the surface of the pretreated modified fiber through a fiber winding device, and modified polypropylene fiber is obtained after curing. The mass ratio of the short fiber to the pretreated modified fiber is 3:1.
[0040] Preparation Example 2 The modified polypropylene fiber is different from the preparation example 1 in that the raw materials and the amounts used are as shown in Table 1. The preparation method thereof comprises the following steps: S1: dispersing 2-bromopropionic acid in anhydrous pyridine to obtain a dispersion, wherein the mass ratio of 2-bromopropionic acid to anhydrous pyridine is 1:5; S2: adding dimethylaminoethyl methacrylate and a catalyst to the dispersion, removing oxygen by nitrogen purging to form an activation solution; S3: adding polypropylene fiber to the activation solution, carrying out graft copolymerization reaction at 75° C. for 8 h, and obtaining pretreated modified fiber after washing and vacuum drying; S4: Shearing the pretreated modified fibers to 3-5 mm to form short fibers; S5: Using the pretreated modified fiber as the main skeleton, the short fiber is wrapped and wound on the surface of the pretreated modified fiber through a fiber winding device, and modified polypropylene fiber is obtained after curing. The mass ratio of the short fiber to the pretreated modified fiber is 3:1.
[0041] Preparation Example 3 The modified polypropylene fiber is different from the preparation example 1 in that the raw materials and the amounts used are as shown in Table 1. The preparation method thereof comprises the following steps: S1: dispersing 2-bromopropionic acid in anhydrous pyridine to obtain a dispersion, wherein the mass ratio of 2-bromopropionic acid to anhydrous pyridine is 1:5; S2: adding dimethylaminoethyl methacrylate and a catalyst to the dispersion, removing oxygen by nitrogen purging to form an activation solution; S3: adding polypropylene fiber to the activation solution, carrying out graft copolymerization reaction at 90° C. for 7 h, and obtaining pretreated modified fiber after washing and vacuum drying; S4: Shearing the pretreated modified fibers to 3-5 mm to form short fibers; S5: Using the pretreated modified fiber as the main skeleton, the short fiber is wrapped and wound on the surface of the pretreated modified fiber through a fiber winding device, and modified polypropylene fiber is obtained after curing. The mass ratio of the short fiber to the pretreated modified fiber is 5:1.
[0042] Preparation Example 4 The modified polypropylene fiber is different from the preparation example 1 in that the raw materials and the amounts used are as shown in Table 1. The preparation method thereof comprises the following steps: S1: dispersing 2-bromopropionic acid in anhydrous pyridine to obtain a dispersion, wherein the mass ratio of 2-bromopropionic acid to anhydrous pyridine is 1:5; S2: adding dimethylaminoethyl methacrylate and a catalyst to the dispersion, removing oxygen by nitrogen purging to form an activation solution; S3: adding polypropylene fiber to the activation solution, carrying out graft copolymerization reaction at 85° C. for 9 h, and obtaining pretreated modified fiber after washing and vacuum drying; S4: Shearing the pretreated modified fibers to 3-5 mm to form short fibers; S5: Using the pretreated modified fiber as the main skeleton, the short fiber is wrapped and wound on the surface of the pretreated modified fiber through a fiber winding device, and modified polypropylene fiber is obtained after curing. The mass ratio of the short fiber to the pretreated modified fiber is 4:1.
[0043] Preparation Example 5 The modified polypropylene fiber is different from that in Preparation Example 1 in that the fiber shearing and fiber winding treatments in Step S4 and Step S5 are not performed, the product of Step S3 is the modified polypropylene fiber, and the other steps are the same as those in Preparation Example 1.
[0044] Preparation Example 6 The modified polypropylene fiber is different from the preparation example 1 in that the preparation method thereof comprises the following steps: S1: cutting the polypropylene fibers into 3-5 mm to form short fibers; S2: Using unsheared polypropylene fiber as the main skeleton, the short fiber is wrapped and wound on the surface of the unsheared polypropylene fiber through a fiber winding device, and the modified polypropylene fiber is obtained after curing. The mass ratio of the short fiber to the unsheared polypropylene fiber is 3:1. Example
[0045] Example 1 A high-performance polypropylene fiber anti-cracking concrete, wherein the raw materials and amounts are shown in Table 2, wherein the anti-cracking agent comprises modified polypropylene fiber and nano-silicon dioxide in a mass ratio of 2.4:1, the modified polypropylene fiber is obtained by Preparation Example 1, and the average particle size of the nano-silicon dioxide is 500nm; the mineral doping material is fly ash; the aggregate is basalt aggregate, including aggregate A and aggregate B in a mass ratio of 4:1, aggregate A is 4.75-9.5mm continuously graded crushed stone, and aggregate B is 9.5-13.2mm continuously graded crushed stone.
[0046] Table 2 The method for preparing the high-performance polypropylene fiber crack-resistant concrete comprises the following steps: S1: Mix cement, aggregate, mineral doping material, modified polypropylene fiber and nano silicon dioxide, and stir evenly to form a premix; S2: Add water to the premix and stir to form an intermediate material; S3: Add water reducing agent and swelling agent to the intermediate material and continue stirring to obtain.
[0047] Example 2 A high-performance polypropylene fiber anti-cracking concrete, which is different from Example 1 in that the raw materials and amounts are shown in Table 2, wherein the anti-cracking agent comprises modified polypropylene fiber and nano-silicon dioxide in a mass ratio of 2.1:1, and the modified polypropylene fiber is obtained by Preparation Example 2; the mineral doping material is silica fume; the aggregate is basalt aggregate, including aggregate A and aggregate B in a mass ratio of 5:1, aggregate A is 4.75-9.5 mm continuously graded crushed stone, and aggregate B is 9.5-13.2 mm continuously graded crushed stone, and other steps are the same as Example 1.
[0048] Example 3 A high-performance polypropylene fiber anti-cracking concrete, which is different from Example 1 in that the raw materials and amounts are shown in Table 2, wherein the anti-cracking agent comprises modified polypropylene fiber and nano-silicon dioxide in a mass ratio of 1.9:1, and the modified polypropylene fiber is obtained by Preparation Example 3; the mineral doping material is natural volcanic ash; the aggregate is basalt aggregate, including aggregate A and aggregate B in a mass ratio of 6:1, aggregate A is 4.75-9.5 mm continuously graded crushed stone, and aggregate B is 9.5-13.2 mm continuously graded crushed stone, and the other steps are the same as Example 1.
[0049] Example 4 A high-performance polypropylene fiber anti-cracking concrete, which is different from Example 1 in that the raw materials and amounts are as shown in Table 2, wherein the anti-cracking agent comprises modified polypropylene fiber and nano-silicon dioxide in a mass ratio of 1.7:1, and the modified polypropylene fiber is obtained by Preparation Example 4; the mineral doping material is granulated blast furnace slag, and the other steps are the same as Example 1.
[0050] Example 5 A high-performance polypropylene fiber anti-cracking concrete, which is different from Example 1 in that the modified polypropylene fiber in the anti-cracking agent is obtained from Preparation Example 5, and the other steps are the same as Example 1.
[0051] Example 6 A high-performance polypropylene fiber anti-cracking concrete, which is different from Example 1 in that the modified polypropylene fiber in the anti-cracking agent is obtained from Preparation Example 6, and the other steps are the same as Example 1.
[0052] Example 7 A high-performance polypropylene fiber crack-resistant concrete, which is different from Example 1 in that the aggregate in the raw material is 4.75-9.5 mm continuously graded basalt aggregate crushed stone, and the other steps are the same as Example 1.
[0053] Example 8 A high-performance polypropylene fiber crack-resistant concrete, which is different from Example 1 in that the aggregate in the raw material is 9.5-13.2 mm continuously graded basalt aggregate crushed stone, and the other steps are the same as Example 1.
[0054] Example 9 A high-performance polypropylene fiber crack-resistant concrete, which is different from Example 1 in that the mineral doping materials in the raw materials are fly ash and silica fume in a mass ratio of 1:1, and the other steps are the same as those in Example 1.
[0055] Example 10 A high-performance polypropylene fiber crack-resistant concrete, which differs from Example 1 in that the mineral doping materials in the raw materials are silica fume, natural volcanic ash and granulated blast furnace slag in a mass ratio of 1:1:1, and the other steps are the same as those in Example 1.
[0056] Embodiment 11 A high-performance polypropylene fiber crack-resistant concrete, which is different from Example 1 in that, in step S1, the modified polypropylene fiber is subjected to the following pretreatment before being mixed with other raw materials to form a premix: The modified polypropylene fiber is subjected to roller hot embossing treatment at 130° C. and 20 KPa to form a grid-like concave-convex texture on the surface of the modified polypropylene fiber.
[0057] Example 12 A high-performance polypropylene fiber crack-resistant concrete, which is different from Example 1 in that, in step S1, the modified polypropylene fiber is subjected to the following pretreatment before being mixed with other raw materials to form a premix: The modified polypropylene fiber is subjected to roller hot embossing treatment at 150° C. and 15 KPa to form a grid-like concave-convex texture on the surface of the modified polypropylene fiber.
[0058] Example 13 A high-performance polypropylene fiber crack-resistant concrete, which is different from Example 11 in that, in step S1, the nano silicon dioxide is subjected to the following pretreatment before being mixed with other raw materials to form a premix: Disperse nano-silicon dioxide in N,N-dimethylformamide at a material-liquid ratio of 1:3.5, add 2-bromoisobutyryl bromide and sodium hydroxide solution, adjust the pH to 8.5, stir and react for 24 hours, and obtain the product after centrifugal separation, drying and grinding. The mass of 2-bromoisobutyryl bromide is 0.15 of the mass of nano-silicon dioxide.
[0059] Comparative Example Comparative Example 1 A high-performance polypropylene fiber crack-resistant concrete, which differs from Example 1 in that the modified polypropylene fiber in the raw material is replaced by ordinary polypropylene fiber with a diameter range of 0.02-0.05 mm and a length range of 19-22 mm, and the other steps are the same as Example 1.
[0060] Comparative Example 2 A high-performance polypropylene fiber crack-resistant concrete, which differs from Example 1 in that no modified polypropylene fiber is added, the modified polypropylene fiber in the raw material is replaced by an equal mass of nano-silicon dioxide, and the other steps are the same as Example 1.
[0061] Comparative Example 3 A high-performance polypropylene fiber anti-cracking concrete, which differs from Example 1 in that no nano-silicon dioxide is added, the nano-silicon dioxide in the raw material is replaced by modified polypropylene fiber of equal mass, and the other steps are the same as Example 1.
[0062] Performance testing A high-performance polypropylene fiber crack-resistant concrete obtained from Example 1-13 and Comparative Example 1-3 was made into standard test blocks according to GB / T50081-2016 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete" and cured for 28 days. The following performance test was then carried out. Each group of tests was carried out 3 times, and the average value of the 3 results was taken as the final result and recorded in Table 3.
[0063] 1. Compression / splitting tensile strength: Refer to standard T / CECS864-2021 "Ultra-High Performance Concrete Test Method Standard" to test the compressive strength and tensile strength of the obtained concrete specimens.
[0064] 2. Total cracking area: Refer to T0573-2020 Test method for early cracking sensitivity of cement concrete (flat plate method) to test the total cracking area per unit area of high-performance polypropylene fiber anti-cracking concrete.
[0065] 3. Fire strength: The cured concrete specimens are placed in a muffle furnace at 600°C for 60 minutes, taken out, and tested for fire strength after natural cooling.
[0066] Table 3 According to the performance test data in Table 3, it can be seen that the high-performance polypropylene fiber crack-resistant concrete of the present application has excellent compressive strength and splitting tensile strength, which shows that the high-performance polypropylene fiber crack-resistant concrete prepared by the preparation method of the present application overcomes the problem of uneven fiber dispersion or difficulty in dispersion, resulting in insufficient bonding between the fiber and the concrete matrix, and significantly improves the crack resistance and durability of the concrete.
[0067] According to the performance test results of Examples 1-4, Examples 5-6, Examples 11-12 and Comparative Examples 1-2, it can be seen that the modification treatment of introducing amino groups on the surface of polypropylene fibers and making a composite fiber structure in which short fibers are wrapped around long fibers can effectively enhance the dispersion of polypropylene fibers in concrete and the bonding strength between the polypropylene fibers and the concrete matrix.
[0068] The surface of the modified polypropylene fiber is pre-treated by hot embossing to form a grid-like concave-convex texture on the surface of the modified polypropylene fiber, which further increases the contact area and mechanical locking force between the fiber and concrete, thereby significantly improving the crack resistance and durability of the concrete.
[0069] At the same time, the introduction of amino groups makes up for the characteristics of polypropylene fiber's low fire resistance and flammability, thereby improving the fire resistance of concrete.
[0070] According to the performance test results of Examples 1-4, Examples 11-13 and Comparative Example 3, it can be seen that the introduction of halogen atoms on the surface of nano-silica can increase the surface activity of nano-silica, further improve the interaction between the nano-silica mixed with modified polypropylene fibers and the concrete matrix, and enhance the chemical bonding between the modified polypropylene fibers and concrete.
[0071] At the same time, the introduction of halogen groups significantly improves the fire resistance of concrete under high temperature conditions, making up for the defects of polypropylene fiber in poor fire resistance and flammability.
[0072] It can be seen from the performance test results of Examples 1-4 and Examples 7-8 that by reasonably matching basalt aggregates of different particle sizes, a multi-level skeleton structure is formed in the concrete, forming a more densely packed concrete structure, which helps to improve the density of the concrete and enhance the comprehensive performance of the concrete.
[0073] It can be seen from the performance test results of Examples 1-4 and Examples 9-10 that the fine particles of various mineral dopants are evenly dispersed in the cement paste, which can become the core for the precipitation of a large amount of hydrates, help to improve the pore structure of the concrete, and make the internal structure of the concrete more uniform and dense, thereby enhancing the durability and crack resistance of the concrete.
[0074] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-performance polypropylene fiber crack-resistant concrete, characterized in that: In terms of weight, the raw materials include 200-300 parts of cement, 600-700 parts of aggregate, 120-180 parts of mineral doping materials, 5-7 parts of water reducing agent, 6-10 parts of expansion agent, 11-16 parts of anti-cracking agent and 86-172 parts of water; The anti-cracking agent is modified polypropylene fiber and nano silicon dioxide in a mass ratio of (1.7-2.4):
1.
2. The high performance polypropylene fiber crack resistant concrete according to claim 1, characterized in that: In parts by weight, the raw materials of the modified polypropylene fiber include 24-29 parts of polypropylene fiber, 16-21 parts of dimethylaminoethyl methacrylate, 0.08-0.14 parts of 2-bromopropionic acid and 0.15-0.25 parts of a catalyst; the catalyst is cuprous bromide and 2,2'-bipyridine in a mass ratio of 1:(1.4-1.8).
3. The high performance polypropylene fiber crack resistant concrete according to claim 2, characterized in that: The preparation method of the modified polypropylene fiber comprises the following steps: S1: dispersing 2-bromopropionic acid in anhydrous pyridine to obtain a dispersion; S2: adding dimethylaminoethyl methacrylate and a catalyst to the dispersion, removing oxygen by nitrogen purging to form an activation solution; S3: adding polypropylene fiber to the activation solution, carrying out graft copolymerization reaction at 75-90° C. for 7-9 hours, and obtaining pretreated modified fiber after washing and vacuum drying; S4: Shearing the pretreated modified fibers to 3-5 mm to form short fibers; S5: Wrapping the short fibers around the surface of the pretreated modified fibers, and obtaining modified polypropylene fibers after curing. The mass ratio of the short fibers to the pretreated modified fibers is (3-5):
1.
4. The high performance polypropylene fiber crack resistant concrete according to claim 1, characterized in that: The aggregate is basalt aggregate, including aggregate A and aggregate B in a mass ratio of (4-6):1; the aggregate A is 4.75-9.5 mm continuously graded crushed stone; the aggregate B is 9.5-13.2 mm continuously graded crushed stone.
5. The high performance polypropylene fiber crack resistant concrete according to claim 1, characterized in that: The mineral doping material is selected from any one or more combinations of fly ash, silica fume, natural volcanic ash and granulated blast furnace slag.
6. The high performance polypropylene fiber crack resistant concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid high efficiency water reducing agent.
7. The high performance polypropylene fiber crack resistant concrete according to claim 1, characterized in that: The expansion agent is a UEA type expansion agent.
8. A method for preparing high-performance polypropylene fiber crack-resistant concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Mix cement, aggregate, mineral doping material, modified polypropylene fiber and nano silicon dioxide, and stir evenly to form a premix; S2: Add water to the premix and stir to form an intermediate material; S3: Add water reducing agent and swelling agent to the intermediate material and continue stirring to obtain.
9. The method for preparing high-performance polypropylene fiber crack-resistant concrete according to claim 8, characterized in that: The modified polypropylene fiber is subjected to the following pretreatment before being mixed with other raw materials to form a premix: The modified polypropylene fiber is subjected to roller hot embossing treatment under the conditions of 130-150° C. and 15-20 KPa, so as to form a grid-like concave-convex texture on the surface of the modified polypropylene fiber.
10. The method for preparing high-performance polypropylene fiber crack-resistant concrete according to claim 8, characterized in that: The nano silicon dioxide is subjected to the following pretreatment before being mixed with other raw materials to form a premix: The nano-silicon dioxide is dispersed in N,N-dimethylformamide, and a halogenating agent and an alkali solution are added, stirred for reaction, and the product is obtained after centrifugal separation, drying and grinding.
Citation Information
Cited By
Large-dosage biomass ash brick as well as preparation method and application thereof
CN120817773A